2004
DOI: 10.1158/0008-5472.can-03-3775
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epidermal Growth Factor Receptor Signaling Protects Human Malignant Glioma Cells from Hypoxia-Induced Cell Death

Abstract: Epidermal growth factor receptor (EGFR) signaling has become an important target for drug development because EGFR signaling enhances tumor cell proliferation, migration, and invasion and inhibits apoptosis. However, the results of clinical trials using EGFR inhibitors in patients with solid tumors have been disappointing. Here, we report a protective effect of the EGFR inhibitors AG1478 and PD153035 against cell death induced by acute hypoxia, which contrasts with their proapoptotic effects under normoxia. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 19 publications
4
80
0
1
Order By: Relevance
“…To induce hypoxia, the PDLFs were transferred to a GasPak pouch, where the total oxygen concentration was reduced to less than 1% (Steinbach et al, 2004), and incubated for the periods indicated. To induce HIF-1α, the PDLFs were incubated for 24 h in the presence of desferoxamine (DFO, 200 μM), a high affinity iron chelator (Hamrick et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…To induce hypoxia, the PDLFs were transferred to a GasPak pouch, where the total oxygen concentration was reduced to less than 1% (Steinbach et al, 2004), and incubated for the periods indicated. To induce HIF-1α, the PDLFs were incubated for 24 h in the presence of desferoxamine (DFO, 200 μM), a high affinity iron chelator (Hamrick et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…EJ bladder carcinoma cells were a gift from M. Eccles (Otago, New Zealand). Cells were cultivated as described before (15). Cell lines were stably transfected by lipofection using FuGENE6 (Roche, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Cell growth and hypoxia was assessed by crystal violet staining as previously described (15). Cell viability was analysed by lactate dehydrogenase (LDH) release assays or flow cytometry (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce hypoxia, the PDLFs were transferred to a GasPak Pouch, where the total oxygen concentration was reduced to less than 1%, and the PDLFs were incubated for the indicated period of time (Steinbach et al, 2004). To induce hypoxia inducible factor (HIF), the PDLFs were incubated for 24 h in the ducible factor (HIF), the PDLFs were incubated for 24 h in the presence of desferoxamine (200 μM), a high affinity iron chelator (Hamrick et al, 2005).…”
Section: Methodsmentioning
confidence: 99%